Lumbar Interverterbral Disc Prolapse (PLID) Surgery and Our Experiences (Journal of Enam Medical College, 2012)
Background: Back pain and sciatica are very common in adult persons. These cause a great loss of working hours with financial loss of individual and the nation. Very careful evaluation must be done to treat these patients. Injudicious treatment, whether medical or surgical, may       aggravate the sufferings.Objective: To study immediate and long term effect of the prolapsed  intervertebral disc surgery.Materials and Methods: This observational study was done in Enam Medical College & Hospital, Savar, Dhaka during January 2007 to June 2011. Sixty four patients operated during this period for prolapsed lumbar intervertebral disc were  included in the study. Fifty six (88%) were male and 8 (12%) were female. Age range was 30  to 50 years. Most of the patients presented with back pain and sciatica with no definite history of trauma or weight lifting. Diagnosis was confirmed by MRI. Results: Sixty (94%) patients had no pain after surgery and only 4 patients had occasional pain. Conclusion: Maintenance of strict criteria for the surgery yields very good result. DOI: http://dx.doi.org/10.3329/jemc.v2i1.11917 J Enam Med Col 2012; 2(1): 20-23